Jambak Jambu Kalko: Nature conservation management of the Serampas of Jambi, Sumatra - BAMBANG HARIYADI (Society for Indonesian Biodiversity, 2012)
Hariyadi B. 2012. Jambak Jambu Kalko: Nature conservation management of the Serampas of Jambi, Sumatra. Biodiversitas 13: 40-45. Serampas is an indigenous group that still inhabits forested areas around the Kerinci Seblat National Park (KSNP) in the island of Sumatra, Indonesia. The group has occupied the area since several centuries ago, long before the KSNP was officially proclaimed as a national park. The blending of local natural conditions, socio-cultural setting and cosmology has gradually produced a number of local wisdoms and practices to manage the local natural resources. The Serampas traditional resource management practices are not only friendly to the environment, but also encourage the more equitable distribution of natural resources among the members of the Serampas community. Jambak jambu kalko is literally means a list of locally important perennial fruit tree species protected by the Serampas customary system. Beyond the jambak jambu kalko the Serampas also recognize customs, traditions, and values that have important role in managing the local natural resources.